Structure of Space Fabric: Meaning of Emptiness - Agrawal , Pramod Kumar (Contemporary Perspective on Science, Technology and Research Vol. 6, 2024)
This study proposes the idea that physical entities such as electrons and cosmological entities like photons operate at distinct levels within the Universe, suggesting they should not be grouped under the same conceptual framework. It posits that what appears to be empty space is, in fact, a complex network made up of cosmological substances. These substances, essentially energy fields, are fundamental components of the cosmological realm. The study introduces the concept that these four fields are diametrically opposed yet collectively maintain equilibrium. It challenges the conventional notion that the space fabric merely fills the emptiness, arguing instead that the space fabric creates the emptiness itself, enabling the propagation of electromagnetic waves and gravitational forces. The paper explores the composition of the space fabric, connecting it to a range of cosmological phenomena, including electromagnetic waves, gravity, light, magnetism, and the enigmatic dark matter and dark energy. Through this exploration, the paper begins to unravel numerous unresolved mysteries. The paper’s philosophical stance is validated by incorporating insights from various disciplines, and its scientific basis is reinforced by aligning with results from well-established experiments.